2016
DOI: 10.1080/07357907.2016.1245317
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia: A Double-Edged Sword in Cancer Therapy

Abstract: Hypoxia is a common feature of malignant tumors. There is an interactive connection between hypoxia and chemoresistance, radioresistance, invasiveness, and angiogenesis. Therefore, tumor hypoxia has been considered as a validated target for treating cancer. This review focuses on the role of hypoxia on chemoresistance and radioresistance. In addition, we address several approaches targeting tumor hypoxia, known as hypoxia-targeted therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
70
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(73 citation statements)
references
References 89 publications
0
70
0
Order By: Relevance
“…Imbalance between oxygen supply and excessive demands in most of solid tumors provoked the hypoxic microenvironment, which in turn played critical roles in promotion of the malignant development in human cancers . Accumulative evidences uncovered the fundamental role of hypoxia in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Imbalance between oxygen supply and excessive demands in most of solid tumors provoked the hypoxic microenvironment, which in turn played critical roles in promotion of the malignant development in human cancers . Accumulative evidences uncovered the fundamental role of hypoxia in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The development of drugs resistance is associated with various factors, including the overexpression of multi-drugs resistance proteins P-gp, the activation of pro-survival signaling pathways and anti-apoptosis proteins, hypoxia, tumor microenvironment and so on. [22][23][24] Previous reports indicated that some CD133 or ALDH positive cancer cells might reveal enhanced capability of sustained growth and drug resistance. 25,26 However, the membranous markers for those drugs resistant cancer cells still remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research showed that ROS level affects the biological processes of tumors, such as apoptosis, genomic instability and neovasculation 15 . On one hand, low ROS level endows tumor cells with properties beneficial for their growth and survival, including radioresistance, chemoresistance and immune evasion 16 . On the other hand, low ROS level has been validated as an effective target for cancer therapy 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, low ROS level endows tumor cells with properties beneficial for their growth and survival, including radioresistance, chemoresistance and immune evasion 16 . On the other hand, low ROS level has been validated as an effective target for cancer therapy 16 , 17 . Covering most cases, senescence is usually related to an induction of ROS.…”
Section: Introductionmentioning
confidence: 99%